An electroencephalogram study on softness cognition of silk fabric hand. Issue 12 (1st December 2016) - Zhang, Xiaoxia; Yue, Jing; Jia, Junjun; Wang, Guohe
Abstract : Fabric hand is a comprehensive sensation when fingers touched the fabrics, and it is an important index in evaluating the comfort of clothes. In this study, electroencephalogram (EEG) method was used to record the brain potentials when people touched and evaluated the fabrics for softness sensation, compared with subjective assessment and physical indicators tested by KES, the results show that Alpha wave's power and the activity area of Alpha rhythm had significant positive correlation with subjective evaluation and physical indicators of fabric softness sensation.